1981
DOI: 10.1111/j.1440-6055.1981.tb01057.x
|View full text |Cite
|
Sign up to set email alerts
|

THE INCIDENCE OF PARASITISM AND DISEASE IN FIELD POPULATIONS OF THE POTATO MOTH PHTHORIMAEA OPERCULELLA (ZELLER) IN AUSTRALIA

Abstract: The incidence of parasitism and disease was recorded during a survey of Phthorimaea operculella populations from the major Australian potato growing areas. High levels of parasitism were found in most regions, though the contribution of each of the three major species showed marked geographic variation. There were also differences in the parasitism of larvae in leaves and in tubers. In some locations larvae were infected by a granulosis virus, which appeared to be endemic at a low frequency throughout the pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 12 publications
5
23
1
Order By: Relevance
“…In 1946 and 1964-66, three exotic parasitoids were introduced into Australia and became successfully established (Callan, 1974). These species, Copidosoma desantisi Annecke & Mynhardt, Apanteles subandinus Blanchard and Orgilus lepidus Muesebeck, are now present throughout the range of P. operculella in various combinations and cause up to 80-90% mortality in local populations (Franzmann, 1980;Briese, 1981). There is, however, a marked difference in the seasonal pattern of parasitization between the warm northern areas (typified by the sites of Tolga, Grantham and Lawrence) and the cooler southern regions in which P. operculella is found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1946 and 1964-66, three exotic parasitoids were introduced into Australia and became successfully established (Callan, 1974). These species, Copidosoma desantisi Annecke & Mynhardt, Apanteles subandinus Blanchard and Orgilus lepidus Muesebeck, are now present throughout the range of P. operculella in various combinations and cause up to 80-90% mortality in local populations (Franzmann, 1980;Briese, 1981). There is, however, a marked difference in the seasonal pattern of parasitization between the warm northern areas (typified by the sites of Tolga, Grantham and Lawrence) and the cooler southern regions in which P. operculella is found.…”
Section: Discussionmentioning
confidence: 99%
“…Field-collected larvae were placed on potato tubers at a density of 1 larva/2 gm potato and allowed to complete their development in the laboratory. Unfortunately, because of the high levels of parasitism at many sites (Briese, 1981), the numbers of adults produced from field-collected larvae were relatively small in some cases (Table I).…”
Section: Methodsmentioning
confidence: 98%
“…Other parasitoids like Tachinidae (Incamyia cuzcensis T.T. and Lixophaga diatraeae Towns), and more than 60 Hymenoptera (Braconidae, Encyrtidae, Eulophidae, Ichneumonidae, Mymaridae, Perilampidae, Pteromalidae, Scelionidae, and Trichogrammatidae) have also been described by several authors (Labeyrie 1959;Lloyd and Guido 1963;Jai Rao 1967;Rao 1967;Rao and Ramachandran-Nair 1967;Leong and Oatman 1968;Rao and Nagaraja 1968;Oatman et al 1969;Lloyd 1972;Odebiyi and Oatman 1972;Cruickshank and Ahmed 1973;Callan 1974;Oatman et al 1974;Oatman and Platner 1974;Cardona and Oatman 1975;Chundurwar 1977Chundurwar , 1978Odebiyi and Oatman 1977;Mitchell 1978;Divakar and Pawar 1979;Franzman 1980;Sankaran and Girling 1980;Briese 1981;Oatman 1982, 1987;Powers and Oatman 1984;Izhevskiy 1985;Horne 1990Horne , 1993. Among all parasitoids listed, there are some ecological differences; for instance, while C. desantisi oviposits in the eggs, A. subandinus and O. lepidus prefer young P. operculella larvae (Platner and Oatman 1972a).…”
Section: Parasitoids and Predatorsmentioning
confidence: 89%
“…However, in some instances, parasitism and predation has been estimated at 40% and 79%, respectively (Coll et al 2000). Level of parasitism was found higher in larvae feeding in the leaves (65%) as compared to larvae infesting tubers (32%) (Briese 1981), suggesting that parasitoids find it easier to encounter the host in exposed potato leaves rather than on tubers buried in the ground. Callan (1974) unsuccessfully tried to correlate parasitism and field damage; he indicated that since parasitism does not lead to instant mortality, it cannot provide immediate control, therefore raising some questions regarding the efficacy of the use of natural enemies.…”
Section: Parasitoids and Predatorsmentioning
confidence: 98%
See 1 more Smart Citation